African Cities and the Development Conundrum (Brill, 2021)
This volume explores some of the complex development challenges associated with the recent and rapid pace of urbanisation across Africa. The transition from a predominantly rural to urban population over the next decade may prompt new approaches and policy responses from the international development community. Readership: Scholars and policy makers interested in Africa, demographic transition, urbanisation, development policy, cities, planning and urban design.